Penile Fractures in Young Bulls Raised in Feedlots in Southern Brazil - Venancio, Fabiano da Rosa; Alberti, Taina dos Santos; Zamboni, Rosimeri; Scheid, Haide Valeska; Ribeiro, Luiza Soares; Sallis, Eliza Simone Viégas; Schild, Ana Lucia (Acta Scientiae Veterinariae, 2022)
Background: Penile fracture is a pathology of young cattle that perform precocious and disordered breeding. The incompatibility of height between males and females and sodomy between males cause a great pressure on the sigmoid flexure and retractor muscle of the penis, which are the main causes and sites of organ injury. This study aimed to describe the epidemiological and pathological aspects of penile fractures observed in young bulls raised in pre-export feedlots (PEFs) in southern Brazil. Cases: In 2 PEFs located in the municipalities of Pelotas (property 1) and Capão do Leão (property 2), 3 male cattle [1 from property 1 and 2 from property 2] presented edema of the foreskin and perineum, associated with dysuria. The evolution of the clinical picture was approximately 20 days in all cases, with evolution to death. The bovine necropsied on property 1 had an increased volume and inguinal edema, involving the penis and scrotal sac. Necrosis of the subcutaneous tissue and local musculature was also observed. The testicles were surrounded by the necrotic tissue, and the right testis was swollen, with flaccid parenchyma adhering to the tunica albuginea. In the necropsy of 1 bull from property 2, an increase in the inguinal volume was observed, with an extensive area of necrosis and edema extending from the prepuce to the caudal musculature of the scrotal sac. There were also marked varicosis in the sigmoid flexure and necrosis of the adjacent region, without the involvement of the corpus cavernosum. During the necropsy of the 2 young bulls, fragments of organs from the abdominal, thoracic, and brain cavities were collected and fixed in 10% buffered formalin. From the bull of the property 2, an anatomical piece consisting of the penis, prepuce, and testicles was also collected and fixed in 10% buffered formalin. After 48 h, the tissue samples were cleaved, embedded in paraffin, cut into 3-µm-thick sections, and stained using hematoxylin and eosin (HE). A histological evaluation of the penile lesions in both cattle revealed intense hemorrhage, congestion, and necrosis of the muscles and tissues adjacent to the corpus cavernosum. In addition to areas of dystrophic calcification, neutrophil and macrophage infiltration was also observed. In the bull from the property 1, an intense edema and proliferation of fibrous tissue surrounding the urethra were noted. There were also marked tubular degeneration and intense infiltration of neutrophils, lymphocytes, and macrophages in the inner portion of the tunica albuginea. Discussion: In the present cases, the diagnosis was based on epidemiological data associated with clinical signs and pathology. The macroscopic lesions observed were probably due to the involvement of blood vessels adjacent to the penis, which suffered trauma during sodomy mating among cattle. These lesions have been described in other reports of this pathology and in diseases, such as acropostitis-phimosis, fibropapilloma of the glans, preputial abscess, and urolithiasis, and the differential diagnosis of these diseases must be carried out, as they have different etiologies. In the bulls of the present study, no lesions were observed in the corpus cavernosum, and this condition was attributed to the presence of varicosis and accumulation of urine in the prepuce, due to the difficulty in exposing the penis. Histologically, there were intense hemorrhage, congestion, and necrosis of the muscles and tissues adjacent to the corpus cavernosum, with the infiltration of neutrophils and macrophages, and areas of dystrophic calcification. The presence of necrotic lesions in tissues adjacent to the penis may be related to hypoxia, vascular lesions, or the action of chemical elements present in the urine. In both cases, vascular lesions were present, which were attributed to the main triggering factor for the disease. Keywords: pre-export feedlots, beef cattle, sodomy, penile trauma.